Sadomasokisme di Indonesia Persepektif HAM dan Hukum Pidana - Fauzi, Inna; Fatmawati, Maria Ulfa (TAWAZUN: Journal of Sharia Economic Law, 2020)
Sexual deviance with forms of violence to get pleasure is an act that links pain and / or shame. This action is a form of sadomasochism. Sadomasochism is two forms of words, namely sadistic and masochistic. Sadistic are those who enjoy sex by giving them pain. Masochists are those who enjoy sex by receiving pain. Masochism is an act that is prohibited under criminal law and is a form of human rights violation. The description above makes the author interested in writing about how human rights and criminal law see the perpetrators of sadomasochism in a husband and wife relationship. This type of writing is a descriptive analysis. Sources of data used are primary data sources and secondary data sources. The method used in this paper is the field observation method. Furthermore, the data obtained were analyzed with the descriptions of the results. The results of the research stated that the perpetrators of sadomasochism in the husband and wife relationship are a prohibited relationship. The perpetrator who gets sexual satisfaction by committing violence against a partner on the basis of human rights is an unfounded form. This is because the act that has been done is also a form of violation of the partner. Sadomasochism is a violation of human rights if there is an element of coercion from either husband or wife, which of course also includes things that are not taught by Islam. In Islam all actions that contain madharat or violence are not allowed. Because what is taught in Islam is gentle and compassionate. In Indonesia alone, 1046 cases have been found related to violence, not only sexual violence but domestic violence as well. Of course this is not a small amount, it needs more intensive handling.